Clinically oriented look into diagnostics and therapy of primary sclerosing cholangitis. Review of literature - Ślósarz, Tymoteusz; Kaczorowski, Rafał; Forenc, Tomasz; Pelczarska, Aleksandra; Krupa, Paulina Maria; Witkowski, Maciej; Mejza, Patryk; Kaczorowska, Anna (Quality in Sport, 2024)
Introduction: Primary sclerosing cholangitis (PSC) is a complex liver disorder marked by multifocal bile duct strictures and dilatations, leading to cholestasis and liver fibrosis. Although the exact cause is unknown, autoimmune mechanisms are strongly suspected. Aim of the Study: This paper reviews current knowledge on PSC, covering its etiology, prevalence, treatment options, and practical management strategies. Current State of Knowledge: PSC management focuses on symptom relief and liver transplantation, with limited success in pharmacological treatments. New therapies, including immune modulators and anti-fibrotic agents, show promise but require further research. Liver transplantation remains the most effective treatment, though recurrence risks necessitate ongoing monitoring. Materials and Methods: This article reviews the current understanding of PSC, including its pathophysiology, diagnostic approaches, clinical features, and management strategies. A comprehensive literature search was conducted using PubMed and Google Scholar, with articles selected based on relevant keywords and evaluated for inclusion in this review. Conclusions: Effective management of PSC necessitates a multidisciplinary approach involving hepatologists, gastroenterologists, radiologists, and transplant surgeons. Ongoing efforts to better understand PSC’s pathogenesis, refine diagnostic methods, and develop more effective therapies are crucial for improving patient outcomes.